2023
DOI: 10.1038/s41598-023-27496-5
|View full text |Cite
|
Sign up to set email alerts
|

Head CT deep learning model is highly accurate for early infarct estimation

Abstract: Non-contrast head CT (NCCT) is extremely insensitive for early (< 3–6 h) acute infarct identification. We developed a deep learning model that detects and delineates suspected early acute infarcts on NCCT, using diffusion MRI as ground truth (3566 NCCT/MRI training patient pairs). The model substantially outperformed 3 expert neuroradiologists on a test set of 150 CT scans of patients who were potential candidates for thrombectomy (60 stroke-negative, 90 stroke-positive middle cerebral artery territory only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…AI is currently being extensively tested regarding its performance in early stroke detection. An AI model outperformed expert readers in detecting early ischemic changes on NCCT in a recent study, 75 and a systematic review including 11 studies and 1976 cases revealed that AI-based ASPECTS performed similar or better than radiologists in identifying early stroke changes on NCCT. 76 Moreover, AI-based NCCT-ASPECTS was reported as good or better as human rating for posterior circulation stroke.…”
Section: Optimization Of Imaging Technology Detection Of Early Ischem...mentioning
confidence: 97%
“…AI is currently being extensively tested regarding its performance in early stroke detection. An AI model outperformed expert readers in detecting early ischemic changes on NCCT in a recent study, 75 and a systematic review including 11 studies and 1976 cases revealed that AI-based ASPECTS performed similar or better than radiologists in identifying early stroke changes on NCCT. 76 Moreover, AI-based NCCT-ASPECTS was reported as good or better as human rating for posterior circulation stroke.…”
Section: Optimization Of Imaging Technology Detection Of Early Ischem...mentioning
confidence: 97%
“…This is not unexpected given that the ML algorithm is derived from a system that was initially developed to detect acute intracranial hemorrhage. In addition, early ischemia may not create CT scan abnormalities that are detectable by even experienced neuroradiologists, even though ischemic stroke may produce severe neurological deficits [21,22]. It is thus possible that cases with early acute ischemia did not result in sufficient CT abnormalities that could be detected by the ML algorithm.…”
Section: Early Ischemic Strokementioning
confidence: 99%
“…However, progress has been made to train an algorithm specifically to detect subtle CT changes from early cerebral ischemia. Our group has created and validated such an algorithm [22]. We foresee aggregating these algorithms to provide a more thorough assessment of patients who present with symptoms that may suggest a stroke.…”
Section: Early Ischemic Strokementioning
confidence: 99%